How do peers promote social inclusion of children with disabilities?A mixed-methods systematic review. Issue 18 (27th August 2020) - Woodgate, Roberta L.; Gonzalez, Miriam; Demczuk, Lisa; Snow, Wanda M.; Barriage, Sarah; Kirk, Susan
Abstract: Purpose: This mixed-methods systematic review synthesized findings from studies published between January 1, 2006 and July 31, 2018 on the social inclusion experiences of children with and without disabilities, as viewed from their own perspective, with a focus on how typically developing peers promote social inclusion. Method: Forty-five studies met the inclusion criteria. Data from included studies were synthesized by means of content analysis. Results: The findings detail the inner social inclusion experiences (e.g., feeling included, different) of children with disabilities and provide information regarding the influence of disability type (e.g., physical, social, affective) on typically developing peers' responses (e.g., acceptance vs. rejection), peers' explanations for social inclusion/exclusion, and peers' relationships with children with disabilities. Barriers to social inclusion, supports, as well as strategies used to promote social inclusion, as perceived by peers and children with disabilities, are also reported. Conclusion: The findings of this review provide evidence that despite society's efforts to promote social inclusion, children with disabilities continue to report feeling lonely and excluded, having limited contact socially outside of home, and encountering systemic barriers (e.g., bullying, discrimination). More research on the social inclusion experiences of children with disabilities beyond educational settings is needed, such as in the contexts of recreation and leisure, community, and employment. Implications for rehabilitation: The perspectives of children with and without disabilities need to be integrated in activities and programs aimed at promoting social inclusion. Teaching social inclusion strategies to children with and without disabilities is needed to help them deal with barriers. In addition to educational settings, rehabilitation clinicians need to promote social inclusion strategies in other contexts such as recreation and leisure, community, and employment contexts.